IMPLEMENTASI PENDIDIKAN KRAKTER DI PONDOK PESANTREN AINUL FALAH BAKIONG GULUK-GULUK SUMENEP - Ach Baidlawi Bukhari; Ach Faisol (LP2M IAIN Sultan Amai Gorontalo, 2025)
This study aims to analyze the implementation of character education at Pondok Pesantren Ainul Falah Bakiong Guluk-Guluk Sumenep, focusing on the concept of character education, its implementation through pesantren regulations, as well as the supporting and inhibiting factors encountered. The main problem underlying this research is the challenge of shaping students’ character in the modern era, which is heavily influenced by technology and social change. Therefore, a consistent character education model based on religious values is required. This research employs a qualitative approach with a descriptive method. The subjects include the pesantren caretakers, teachers, students, and parents. Data were collected through observation of pesantren activities, in-depth interviews, and documentation of the regulations and pesantren archives. Data analysis was carried out using Miles & Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing, while data validity was ensured through source and method triangulation. The findings reveal that character education at Pondok Pesantren Ainul Falah is implemented through regulations, role modeling by teachers, as well as habituation of religious practices and social activities. Core values fostered include honesty, discipline, responsibility, cleanliness, and politeness. Supporting factors consist of the exemplary role of caretakers, pesantren culture, and parental support. The inhibiting factors involve technological influence, diverse family backgrounds, and limited facilities, which are addressed through digital literacy programs, personal counseling, and facility improvement. Keywords: character education; pesantren; regulations; honesty; discipline